2022
DOI: 10.3389/fpubh.2022.944071
|View full text |Cite
|
Sign up to set email alerts
|

Trends in anti-HER2 drugs consumption and influencing factors

Abstract: BackgroundHuman epidermal growth factor receptor 2 (HER2) inhibitors have been approved to treat various cancers with HER2 amplification. The Chinese government has made great efforts to improve the availability and affordability of these drugs. This study aimed to analyze the trends in anti-HER2 drug consumptions in Nanjing from 2012 to 2021, and explore influencing factors.MethodsData about use of anti-HER2 drugs in 2012–2021 were extracted from Jiangsu Medicine Information Institute. Six types of anti-HER2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…Consistently, previous studies have indicated that drug price was an important determinant of drug consumption, and there was a negative relationship between DDC and the number of DDDs (11,13,24). In order to improve the availability and affordability of drugs, China established its fundamental health insurance system in 2009, which was enhanced by the implementation of price negotiation and mandatory reimbursement policies in 2017 (13). The policies of price negotiation have been implemented in many countries, which resulted in a significant reduction in drug prices and an increase in drug consumption (24, 25).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Consistently, previous studies have indicated that drug price was an important determinant of drug consumption, and there was a negative relationship between DDC and the number of DDDs (11,13,24). In order to improve the availability and affordability of drugs, China established its fundamental health insurance system in 2009, which was enhanced by the implementation of price negotiation and mandatory reimbursement policies in 2017 (13). The policies of price negotiation have been implemented in many countries, which resulted in a significant reduction in drug prices and an increase in drug consumption (24, 25).…”
Section: Discussionsupporting
confidence: 82%
“…DDC is an efficient indicator that guides the market prices of pharmaceutical products (15). Consistently, previous studies have indicated that drug price was an important determinant of drug consumption, and there was a negative relationship between DDC and the number of DDDs (11,13,24). In order to improve the availability and affordability of drugs, China established its fundamental health insurance system in 2009, which was enhanced by the implementation of price negotiation and mandatory reimbursement policies in 2017 (13).…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…For example, Jiang [16] conducted a study on the accessibility of anticancer medicines and found that the NDPN policy increased the affordability and accessibility of these medicines for patients. Other scholars, such as Huang [17], Liu [18], Zhang [19], Liu [20], Zhu [21], Sun [22], Cai [23], Fang [24], Diao [25], and Ding [26], have investigated the use of NDPN anticancer medicines by utilising hospital procurement data and employing interrupted time series methods. Their results indicated that the implementation of the NDPN policy resulted in a noticeable increase in the use of anticancer medicines, accompanied by a further decrease in drug costs.…”
Section: Introductionmentioning
confidence: 99%